2018
DOI: 10.1152/ajpregu.00405.2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPV1 in acupuncture modulation of reflex excitatory cardiovascular responses

Abstract: We have shown that acupuncture, including manual and electroacupuncture (MA and EA), at the P5-6 acupoints stimulates afferent fibers in the median nerve (MN) to modulate sympathoexcitatory cardiovascular reflexes through central regulation of autonomic function. However, the mechanisms underlying acupuncture activation of these sensory afferent nerves and their cell bodies in the dorsal root ganglia (DRG) are unclear. Transient receptor potential vanilloid type 1 (TRPV1) is present in sensory nerve fibers dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 44 publications
6
30
0
1
Order By: Relevance
“…The method used for manual acupuncture in our study (at~2 Hz for 5 min every 10 min during a 30-min period) has been reported in many other papers (1,16). Importantly, we observed increased discharges of the afferent fiber in the median nerve during manual acupuncture stimulation, while the afferent activity stopped after manual acupuncture (2). Thus, we believe that neural pathways involved in acupuncture stimulation mainly contribute to acupuncture's action in the regulation of cardiovascular function.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The method used for manual acupuncture in our study (at~2 Hz for 5 min every 10 min during a 30-min period) has been reported in many other papers (1,16). Importantly, we observed increased discharges of the afferent fiber in the median nerve during manual acupuncture stimulation, while the afferent activity stopped after manual acupuncture (2). Thus, we believe that neural pathways involved in acupuncture stimulation mainly contribute to acupuncture's action in the regulation of cardiovascular function.…”
supporting
confidence: 70%
“…This assumption is supported by numerous publications (6,7,9,10,14). In addition, as we have addressed in our paper, not only mechanical stimulation, but also the chemical substances generated during the insertion and/or manipulation of the acupuncture needle, likely contribute to activation of sensory afferent nerves that send inputs to the central nervous system, leading to regulation of cardiovascular function (2).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…The P6 acupoint is located on the forelimb 1.0 mm above the flexor crease in the paw overlying the median nerve (Figure ) (Hua, ). MA (~2 Hz) applied at this acupoint evokes median nerve discharge and attenuates reflex cardiovascular responses (Guo, Fu, Su, Tjen‐A‐Looi, & Longhurst, ; Zhou, Fu, Tjen‐A‐Looi, Li, & Longhurst, ). A stainless steel acupuncture needle (40‐gauge, 0.16 × 15 mm) was inserted (2–3 mm) at P6.…”
Section: Methodsmentioning
confidence: 99%
“…TO THE EDITOR: Acupuncture is a traditional form of Asian medicine; theoretically the practice involves inserting a needle at the invisible acupoints on the top of the skin for therapeutic purposes. In a recent article by Guo et al (1), it was reported that manual acupuncture on the wrist area of rats in which the P6 acupoint was the proposed site and the median nerve was anatomically located, contributed to the inhibition of reflex increases in blood pressure, when compared with electrical and sham acupuncture. In this letter, I express my opinions, respectfully, on the findings.…”
mentioning
confidence: 99%